Le crépuscule des lieux communs ou les stéréotypes entre consensus, certitude et doute - Oesch-Serra, Cecilia; Py, Bernard (My University, 1997)
This paper analyses the social representations, through their verbal expression, of the immigrant's discourse from «Abruzzi» (in Italy), still living in Neuchâtel or being back to their country of birth. Two aspects have been particularly studied: on the one hand a best knowledge of the immigrant's daily culture and on the other hand, the stereotypes undertaking's process by the speakers themselves.This study, based on transcriptions of non-structured interviews allows to sketch a typology of the enunciative relations between speakers and stereotypes, between the immediate adherence to stereoptypes and their total or partial opposition.